Modelling Factors Influencing Bank Customers’ Readiness for Artificial Intelligent Banking Products - Garekwe, L.; Ferreira-Schenk, S. J.; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2024)
In the era of globalisation and technological development, artificial intelligence (AI) plays a significant role in financial activities and services. AI in financial technology has a clear potential to accelerate the financial industry's transformation by offering excellent value to customers by providing tailor-made products and services, thus improving customer experience. The paper aims to model the factors influencing bank customers' readiness for artificially intelligent banking products within the South African banking sector. Data were collected from 346 banking customers within South Africa. The study results revealed that demographic and socio-cultural variables influence the readiness for artificially intelligent banking products. Behavioural finance biases also influence bank customers' readiness for artificially intelligent banking products. Furthermore, the study also found that customers' readiness for artificial intelligent banking products is faced with the limitation of the inaccessibility to technological tools in rural areas. Consequently, policies that can improve infrastructure and enable rural citizens to cope with advanced technology can improve bank customers' readiness for artificially intelligent banking products in South Africa.